Characterization of Soybean Genetically Modified for Drought Tolerance in Field Conditions - Fuganti-Pagliarini, Renata; Ferreira, Leonardo C.; Rodrigues, Fabiana A.; Molinari, Hugo B. C.; Marin, Silvana R. R.; Molinari, Mayla D. C.; Marcolino-Gomes, Juliana; Mertz-Henning, Liliane M.; Farias, José R. B.; de Oliveira, Maria C. N.; Neumaier, Norman; Kanamori, Norihito; et al. (Frontiers in Plant Science, 2017)
Drought is one of the most stressful environmental factor causing yield and economic losses in many soybean-producing regions. In the last decades, transcription factors (TFs) are being used to develop genetically modified plants more tolerant to abiotic stresses. Dehydration responsive element binding (DREB) and ABA-responsive element-binding (AREB) TFs were introduced in soybean showing improved drought tolerance, under controlled conditions. However, these results may not be representative of the way in which plants behave over the entire season in the real field situation. Thus, the objectives of this study were to analyze agronomical traits and physiological parameters of AtDREB1A (1Ab58), AtDREB2CA (1Bb2193) and AtAREB1 (1Ea2939) GM lines under irrigated (IRR) and non-irrigated (NIRR) conditions in a field experiment, over two crop seasons and quantify transgene and drought-responsive genes expression. Results from season 2013/2014 revealed that line 1Ea2939 showed higher intrinsic water use and leaf area index. Lines 1Ab58 and 1Bb2193 showed a similar behavior to wild-type plants in relation to chlorophyll content. Oil and protein contents were not affected in transgenic lines in NIRR conditions. Lodging, due to plentiful rain, impaired yield from the 1Ea2939 line in IRR conditions. qPCR results confirmed the expression of the inserted TFs and drought-responsive endogenous genes. No differences were identified in the field experiment performed in crop season 2014/2015, probably due to the optimum rainfall volume during the cycle. These field screenings showed promising results for drought tolerance. However, additional studies are needed in further crop seasons and other sites to better characterize how these plants may outperform the WT under field water deficit.